Brunner's gland hamartoma presenting as gastric outlet obstruction: unusual presentation and review of literature. (January 2020) - Gupta, Amit; Rajput, Depak; Kumar, Utkarsh; Gupta, Sweety; Singh, Ashok; Sanyal, Sumit
Brunner's gland hamartoma (or Brunneroma) is an uncommon tumour with an incidence of <0.01%, accounting for approximately 5–10% of benign duodenal tumours. Usually asymptomatic, it may manifest occasionally with duodenal obstruction or upper gastrointestinal haemorrhage and rarely with biliary fistulation, cholestatic jaundice and intussusception. It may be associated with uraemia and chronic pancreatitis. The diagnosis is usually confirmed by imaging studies and upper gastrointestinal endoscopy. Surgical excision or endoscopic resection is preferred for symptomatic large hamartomas. Here we report a case of 45-year-old man presenting with features of pancreatitis and gastric outlet obstruction due to a large Brunner's gland hamartoma, on his endoscopic, radiologic, surgical and pathologic findings.